Healing with precision - Robotic Mitrofanoff procedure with autologous pubovaginal sling in neurogenic incontinence - Sidhartha Kalra; Siddhant Bolar; Rajat Mudhol; Shiva Gour (Indian Journal of Urology)
A 21-year-old obese female presented with urinary incontinence and lower limb weakness after a D11-L3 laminectomy for spinal teratoma. Evaluation revealed a patulous urethra with video-urodynamic study suggestive of hyposensory, hypocontractile bladder of 500 ml capacity with open bladder neck, intrinsic sphincter deficiency, and good compliance. Due to obesity, perineal hypoesthesia, and clean intermittent catheterization (CIC) challenges, a robotic Mitrofanoff channel and continent bladder neck (tensor fascia lata graft) were planned. Tension-free channel was achieved by removing one row of staples to increase channel length, use of indocyanine green intraoperatively to assess vascularity, and umbilicus as site of Mitrofanoff to avoid thick pannus. At 3-months’ follow-up, the patient performed CIC comfortably every 5 h and was continent.